Uji Dosis Tepung Buah Sirih Hutan (Piper Aduncum L.) terhadap Mortalitas Hama Sitophilus Oryzae L. Pada Beras di Penyimpanan - Rustam, Rusli; Andrianto, Benny Salvino; Sutikno, Agus (Jurnal Agro Teknologi Tropika, 2017)
Research aims to obtain dose of spiked pepper fruit flour (Piper aduncum L.) better ofÂ  imago S. oryzae on the rice. Research conducted at the laboratory of plant pests, Faculty of Agriculture, University of Riau from May to June 2015. The Research was conducted experimentally by using completely randomized design (CRD), which consists of 5 treatments, where each treatments was repeated 4 times to obtain 20 units experiment. The treatment used in the research is (0 g/ 100 g, 2 g/ 100 g, 4 g/ 100 g, 6 g/ 100 g, 8 g/ 100 g of rice). Data obtained analyzed statistically using analysis of variance followed by least significant difference (LSD) at 5%. Dose applications of spiked pepper fruit flour at doses 6 g/ 100 g rice better ofÂ  imago S. oryzae with lethal time50 24,5 hour and mortality by 97,5% inhibit the growth of the population, shrinkage weight of rice, and lethal dose95 by 4,5%.